Buildings on South Main Street in Old Salem, 1964. - (:unkn) unknown (Forsyth County Public Library)
WSJ 1-3-64 p.11.
The center building is home to Dan's Antique Shop, which was Winkler Bakery. The small shop to the left is a hat shop. The Butner House is at the far left. These buildings have recently been purchased by Old Salem.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth